Genetic and Phenotypic Basis of Autosomal Dominant Parkinson's Disease in a Large Multi-Center Cohort - Lesage, Suzanne; Houot, Marion; Mangone, Graziella; Tesson, Christelle; Bertrand, Hélène; Forlani, Sylvie; Anheim, Mathieu; Brefel-Courbon, Christine; Broussolle, Emmanuel; Thobois, Stéphane; Damier, Philippe; Durif, Franck; et al. (Frontiers in Neurology, 2020)
LRRK2, SNCA and VPS35 are unequivocally associated with autosomal dominant Parkinson’s disease (PD). We evaluated the prevalence of LRRK2, SNCA and VPS35 mutations and associated clinical features in a large French multi-center cohort of PD patients. Demographic and clinical data were collected for 1805 index cases (592 with autosomal dominant inheritance and 1213 isolated cases) since 1990. All probands were screened with TaqMan assays for LRRK2 Gly2019Ser. In the absence of this mutation, the coding sequences of the three genes were analyzed by Sanger sequencing and/or next-generation sequencing. The data for the three genes were analyzed according to age at onset, family history, ethnic origin and clinical features. We identified 160 index cases (8.9%) with known pathogenic variants: 138 with pathogenic LRRK2 variants (7.6%), including 136 with the Gly2019Ser mutation, 19 with SNCA point mutations or genomic rearrangements (1.1%), and three with the VPS35 Asp620Asn mutation (0.16%). Mutation frequencies were higher in familial than isolated cases, consistent with autosomal dominant inheritance (12.0% vs. 7.3%; OR 1.7, 95% CI [1.2-2.4], p = 0.003). PD patients with LRRK2 variants were more likely to have higher rates of late-onset PD (> 50 years; OR 1.5, 95% CI [1.0-2.2], p = 0.03), whereas those with SNCA mutations tended to have earlier age at onset disease (≤ 50 years, p = 0.06). The clinical features of LRRK2 carriers and those without any pathogenic variants in known PD-associated genes were similar. The likelihood of detecting disease-causing mutations was higher in cases compatible with autosomal dominant inheritance.